2016
DOI: 10.18632/oncotarget.7866
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plasma microRNA expression profiles revealed different cancer susceptibility in healthy young adult smokers and middle-aged smokers

Abstract: Cigarette smoking is a world-wide habit and an important risk factor for cancer. It was known that cigarette smoking can change the expression of circulating microRNAs (miRNAs) in healthy middle-aged adults. However, it remains unclear whether cigarette smoking can change the levels of circulating miRNAs in young healthy smokers and whether there are differences in cancer susceptibility for the two cases. In this study, the miRNA expression profiles of 28 smokers and 12 non-smokers were determined by Agilent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Interestingly, nicotine shows an ability of decreasing ACE2 expression, suggesting a possible role of anti-2019-nCoV. This finding may be consistent with our previous report that smoking-inhibited miRNAs are significantly associated with SARS [27]. For the biologics, previous reports supported the prediction for lipopolysaccharide [28].…”
Section: The Jmap Agents That Decrease Ace2 Expressionsupporting
confidence: 90%
“…Interestingly, nicotine shows an ability of decreasing ACE2 expression, suggesting a possible role of anti-2019-nCoV. This finding may be consistent with our previous report that smoking-inhibited miRNAs are significantly associated with SARS [27]. For the biologics, previous reports supported the prediction for lipopolysaccharide [28].…”
Section: The Jmap Agents That Decrease Ace2 Expressionsupporting
confidence: 90%
“…To our knowledge, this study is the first study to demonstrate that miR-34b-5p may be involved in the pathogenesis of ALV-J, as it appears to affect many aspects of cancer biology, such as cell proliferationand cell cycle progression. We further investigated the biological functions of miR-34b-5p using an overexpression experiment (Zhao et al, 2015 ; Shi B. et al, 2016 ). The functional investigation demonstrated that ectopic expression of miR-34b-5p could accelerate cell proliferation and migration in ALV-J-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that cigarette smoking can change microRNA profile in many human organs and induces the change of plasma miRNA expression profiles in healthy subjects. Using microarray, Shi and co-authors [ 82 ] identified 24 up-regulated and 11 down-regulated plasma miRNAs in young healthy smokers. The authors concluded that the changes in miRNA expression profile caused by smoking can be viewed as risk factors for cancers (especially leukemia and lymphoma), cardiovascular disease, and metabolic syndrome in young adult smokers.…”
Section: Effects Of Xenobiotics On Mirna Expressionmentioning
confidence: 99%